Utilization of Microservices for E-portfolio Digital Document Management Based on Telegram Bot - Mochammad Choirul Anam; irwan (Procedia of Engineering and Life Science, 2022)
In the current era of globalization, people's needs for information technology are increasing. This can be seen from the community's behavior in responding to various events that occur, especially during the current pandemic. Many large companies make it easy for people to connect through social media. One of the social media available is a telegram. Educational institutions also use Telegram as a means of information and education. Besides that, telegram bots also play an important role in answering common questions that are often developed so that institutions do not need to answer them manually. The method used is RAD (Rapid Application Development) and black box testing by utilizing microservices to manage digital E-Portfolio documents used by students to support learning activities. Using the telegram bot makes it easier for students to upload digital documents to the e-Portfolio platform. Moreover, utilizing the microservice architecture can reduce the server load when accessed simultaneously and is more secure because the database layer is separate from the interface layer accessed by the user.